2007
DOI: 10.1016/j.tiv.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle effects on rat alveolar epithelial cell monolayer barrier properties

Abstract: Inhaled nanoparticles have been reported to contribute to deleterious effects on human health. In this study, we investigated the effects of ultrafine ambient particulate suspensions (UAPS), polystyrene nanoparticles (PNP; positively and negatively charged; 20, 100, 120 nm), quantum dots (QD; positively and negatively charged; 30 nm) and single wall carbon nanotubes (SWCNT) on alveolar epithelial cell barrier properties. Transmonolayer resistance (Rt) and equivalent shortcircuit current (Ieq) of primary rat al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 57 publications
0
39
1
Order By: Relevance
“…Some nanoparticles could pass the blood-brain barrier and cause brain toxicity ( Figure 2); of course more studies are required. [22][23][24] Due to the high loading of nanoparticles, macromolecule absorption will increase, so that they can cross through the digestive tract. Because, for example, lectin is such an immunologic material for coating, it can be toxigenic and also cause inflammatory responses or digestive stimulation.…”
Section: Toxicity Of Nanoparticlesmentioning
confidence: 99%
“…Some nanoparticles could pass the blood-brain barrier and cause brain toxicity ( Figure 2); of course more studies are required. [22][23][24] Due to the high loading of nanoparticles, macromolecule absorption will increase, so that they can cross through the digestive tract. Because, for example, lectin is such an immunologic material for coating, it can be toxigenic and also cause inflammatory responses or digestive stimulation.…”
Section: Toxicity Of Nanoparticlesmentioning
confidence: 99%
“…They found that R t was reduced after apical exposure of rat alveolar cell epithelia monolayers to a variety of nanomaterials, including ultrafine ambient particulate suspensions, positively charged quantum dots, and single-walled carbon nanotubes at varying concentrations. 11 In turn, other research groups have investigated the interaction of silver nanoparticles on voltage-activated Na + currents in hippocampal CA1 neurons, with results indicating that silver nanoparticles may alter the action potential of these neurons by reducing voltage-gated sodium currents. 12 Even though there have been many advances in the area of bionanoscience, there is still very little known about the complex interaction of nanoparticles with the cell membrane on airway epithelial cells, and the effect that this interaction can have on many diverse cellular processes.…”
Section: Cftr CLmentioning
confidence: 99%
“…14,15 However, hydrophobic NPs may induce genotoxicity, carcinogenicity, and teratogenicity; therefore, a hydrophilic surface is preferred over the hydrophobic surface for biomedical applications. [16][17][18][19] Consequently, numerous efforts have been focused on refining the properties of metal NPs through modification of their synthesis methods from conventional methods to green ones. Some of these include the use of seaweed, 20 tea, 21,22 as well as peel extracts of plantain, 23 banana, 24 and orange.…”
Section: Introductionmentioning
confidence: 99%